The Microstructure of WE43 MMC Reinforced with SiC Particles - Dybowski B. (Archives of Metallurgy and Materials, 2016)
It is well known that the properties of a metal matrix composites depend upon the properties of the reinforcement phase, of the matrix and of the interface. A strong interface bonding without any degradation of the reinforcing phase is one of the prime objectives in the development of the metal matrix composites. Therefore, the objective of this work is to characterize the interface structure of WE43/SiC particles composite. Magnesium alloys containing yttrium and neodymium are known to have high specific strength, good creep and corrosion resistance up to 250°C. The addition of SiC ceramic particles strengthens the metal matrix composite resulting in better wear and creep resistance while maintaining good machinability. In the present study, WE43 magnesium matrix composite reinforced with SiC particulates was fabricated by stir casting. The SiC particles with 15 μm, 45 μm and 250 μm diameter were added to the WE43 alloy. The microstructure of the composite was investigated by optical microscopy, scanning electron microscopy, scanning transmission electron microscopy and XRD analysis. YSi and Y2Si reaction products are observed at the interfaces between SiC particles and WE43 matrix in the composite stirred at 780°C. Microstructure characterization of WE43 MMC with the 45 μm, stirred at 720°C showed relative uniform reinforcement distribution. Moreover, the Zr-rich particles at particle/matrix interface were visible instead of Y-Si phases. In the case of composite with 15 μm particles the numerous agglomerates and reaction products between SiC particles and alloying elements were observed. The presence of SiC particles assisted in improving hardness and decreasing the tensile strength and plastic properties.